2010
DOI: 10.1155/2010/850541
|View full text |Cite
|
Sign up to set email alerts
|

Taenia crassicepsInfection Attenuates Multiple Low-Dose Streptozotocin-Induced Diabetes

Abstract: Taenia crassiceps, like other helminths, can exert regulatory effects on the immune system of its host. This study investigates the effect of chronic T. crassiceps infection on the outcome of Multiple Low Dose Streptozotocin-Induced Diabetes (MLDS). Healthy or previously T. crassiceps-infected mice received MLDS and type 1 diabetes (T1D) symptoms were evaluated for 6 weeks following the induction of MLDS. T. crassiceps-infected mice displayed lower blood glucose levels throughout the study. A significantly low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 46 publications
(58 reference statements)
3
38
0
1
Order By: Relevance
“…In addition, clinical trials in humans examining effects of helminth products on disease severity in autoimmune diseases have shown promising results, as well as showing the safety of these helminth-derived immunomodulators for use as therapeutic agents. Although there is evidence to show that helminth infection can prevent T1DM in mice, 11,13,[23][24][25] there are no reports to support this hypothesis in humans. Epidemiologic studies carried out in southern India have shown reduced prevalence of LF after mass drug administration.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, clinical trials in humans examining effects of helminth products on disease severity in autoimmune diseases have shown promising results, as well as showing the safety of these helminth-derived immunomodulators for use as therapeutic agents. Although there is evidence to show that helminth infection can prevent T1DM in mice, 11,13,[23][24][25] there are no reports to support this hypothesis in humans. Epidemiologic studies carried out in southern India have shown reduced prevalence of LF after mass drug administration.…”
Section: Discussionmentioning
confidence: 99%
“…As Treg cells play an important regulatory role against diabetogenesis (Brode et al, 2006;Ott et al, 2005), some authors suggest that they are also responsible for the anti-diabetogenic effects of helminths (Hübner et al, 2009;Zaccone et al, 2009). However, other reports do not support the importance of Treg cells Espinoza-Jiménez et al, 2010). This inconsistency probably suggests the presence of distinct suppressive mechanisms in each parasite species.…”
Section: Experimental T1dmentioning
confidence: 89%
“…In line with this, there has been an increasing trend of patients with ADs exhibiting an ever-decreasing incidence of parasitic infections in developed countries and regions (3). Furthermore, previous epidemiological studies have indicated the reduced incidence of ADs in poorly endemic regions (21,22). Therefore, the concept of an inverse relationship between the global distribution of ADs and the parasitic infections has been widely presented and is known the 'Hygiene hypothesis'.…”
Section: Hygiene Hypothesismentioning
confidence: 92%
“…Another study suggested that the depletion of organisms from the urban environment in wealthy areas as one of the main reasons for the increased prevalence of chronic inflammatory disorders (25). Subsequently, various epidemiological and experimental studies confirmed the protective role of parasites and their excretory/secretaries upon various ADs, including type 1 diabetes mellitus, multiple sclerosis, RA and autoimmune thyroid disease (22,26,27). Furthermore, studies have shown that modulation of the host immune response by parasitic helminthes may have a concomitant health benefit as it may protect helminthes from being eradicated, and simultaneously protect the host from excessive pro-inflammatory responses (28,29).…”
Section: Hygiene Hypothesismentioning
confidence: 99%